"Benign" tremor? A serial case report of 2.5 year progression from mild cognitive impairment to amnestic dementia following deep brain stimulator placement for essential tremor. Issue 5 (3rd September 2022) - Gallagher, Virginia T.; Obolsky, Maximillian A.; Soble, Jason R.
Abstract: Essential tremor (ET) is a prevalent neurological disorder with associated neuropsychological sequalae. Although cognitive deficits associated with ET are traditionally conceptualized as attention, processing speed, and executive impairments attributed to underlying frontal-subcortical dysfunction, emerging literature highlights the elevated frequency of progressive amnestic memory impairments in patients with ET. This case study centers around a 75-year-old woman with a 15-year history of ET who underwent deep brain stimulation (DBS) as well as three neuropsychological evaluations, one pre-surgically and two post-surgically at one and two-years post successful DBS surgery. Neuropsychological evaluation results revealed circumscribed mild and variable memory deficits pre-surgically and one-year post-surgically, However, two-years post-DBS, reliable change indices revealed significant declines in verbal/visual memory, consistent with an amnestic presentation, in addition to executive functions, aspects of higher-level language abilities, and overall IQ. This case study adds to a growing literature identifying a subset of ET patients with a neurodegenerative cognitive trajectory characterized by progressive, amnestic memory impairment. The case also highlights the importance of serial monitoring of cognition beyond the pre-surgical DBS workup to monitor for clinically significant decline(s).